HUMMING BIRD SEARCH ALGORITHM - Singh, Sanjana; Bhardwaj, Surbhi; Mudgil, Shivansh (IJRDO -Journal of Computer Science Engineering, 2015)
Google Hummingbird is a search algorithm used by Google.Google started using Hummingbird about August 30, 2013, and announced thechange on September 26 on the eve of the company's 15th anniversary.Gianluca Fiorelli said Hummingbird is about synonyms but also about context.Google always had synonyms, he writes, but with Hummingbird it is also able tojudge context - thereby judging the intent of a person carrying out a search, todetermine what they are trying to find out. Danny Sullivan said of Hummingbird,"Google said that Hummingbird is paying more attention to each word in a query,ensuring that the whole query — the whole sentence or conversation or meaning— is taken into account." Michelle Hill said Hummingbird is about"understanding intent". Steve Masters wrote, "The Hummingbird approachshould be inspirational to anyone managing and planning content — if you aren'talready thinking like Hummingbird, you should be. In a nutshell, think about whypeople are looking for something rather than what they are looking for. A contentstrategy should be designed to answer their needs, not just provide them withfacts." "The age of Semantic Search.“Hummingbird” is the name of the new search platform that Google is using asof September 2013, the name comes from being “precise and fast” and is designed